An evaluation of just in time (JIT) implementation on manufacturing performance in Indian industry. Issue 3 (2014) - Gurinder Singh; Inderpreet Singh Ahuja
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to create awareness of contributions made by just‐in‐time manufacturing (JIT) practice towards building performance measures in Indian manufacturing industry. Implications of JIT implementation issues in Indian manufacturing industry have been critically evaluated in this paper. Design/methodology/approach – While conducting this study, survey of reasonable number of manufacturing organisations have been made so as to ascertain contributions made by JIT initiatives in the Indian manufacturing industries for achieving major performance measures. The correlations between various JIT implementation dimensions and performance parameters have been worked out by employing various statistical tools and bringing out significant factors contributing effectively towards achieving manufacturing performance measures. Findings – The study divulges that attitude of management, participation of workers, relationship of organisation with suppliers and customers, adoption of latest manufacturing methods and successful adaptation of effective JIT initiatives can significantly contribute towards enhancing performance measures in the organisation. The study also reveals that the holistic JIT manufacturing methods outscore the traditional manufacturing practices towards improving the manufacturing performance. The study highlights that detailed JIT implementation over a reasonable period can greatly contribute towards achievement in performance of organisation. Originality/value – The present study analyses the impact of JIT manufacturing method on performance of organisation and highlights the need for aligning organisational efforts in establishing manufacturing methods for attaining improvements in performance of manufacturing organisations. The paper highlighted the status of JIT manufacturing initiatives in the Indian context and the preparedness of Indian manufacturing industry to meet the challenges imposed by the Western world by employing aggressive JIT manufacturing strategies.